1999
DOI: 10.1161/01.cir.99.7.949
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of a Segment of Slow Conduction on Reentrant Ventricular Tachycardia in the Rabbit Heart

Abstract: Background-The purpose of this study was to compare differential effects of a segment of slow conduction during ventricular tachycardia (VT) due to depression of the action potential and electrical uncoupling. Methods and Results-In 33 Langendorff-perfused rabbit hearts, a ring of anisotropic left ventricular subepicardium was created by a cryoprocedure. Reentrant VT was produced by incremental pacing. Slow conduction in a segment of the ring was created by selective perfusion of the LAD with 10 mmol/L potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Heptanol is a lipophilic agent known to reversibly inhibit gap junctions and it has been used frequently as an uncoupler to investigate the role of cellular coupling in the induction of re‐entrant arrhythmias 16–18 . It has been shown that heptanol limits myocardial infarct size when infused before ischaemia 19 or during reperfusion 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Heptanol is a lipophilic agent known to reversibly inhibit gap junctions and it has been used frequently as an uncoupler to investigate the role of cellular coupling in the induction of re‐entrant arrhythmias 16–18 . It has been shown that heptanol limits myocardial infarct size when infused before ischaemia 19 or during reperfusion 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In both normal dog hearts [6] and the canine model of healed myocardial infarction [7] selective intracoronary infusion of heptanol increases the susceptibility to arrhythmias, consistent with altered cellular coupling being an important risk factor for arrhythmogenesis [37]. Furthermore, in perfused rabbit heart epicardial preparations the arrhythmias produced by heptanol are likely to be re-entrant ventricular tachycardias (VT) [14]. Whilst heptanol is relatively selective in its actions on gap junctions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to patients with ischemic cardiomyopathy, patients in whom no sites with IPs were identified during mapping of VT had a high probability of recurrent VT 3 . Major complications associated with the failure to eliminate inducible VTs by ablation have been described previously in patients with nonischemic cardiomyopathy 9–11 . It is possible that systematic epicardial mapping in all patients would have revealed IPs in some of the patients who did not have endocardial IPs.…”
Section: Discussionmentioning
confidence: 88%